Schwannoma in the Midline of Hard Palate: A Case Report and Review of Literature - Monir Moradzadeh Khiavi; Ali Taghavi Zenouz; Ali Hossein Mesgarzadeh; Omid Sabetmehr; Seyyed Mostafa Mahmoudi; Maryam Kouhsoltani (Tabriz University of Medical Sciences, 2014)
Schwannoma is a benign encapsulated slow-growing tumor that originates from Schwann cells of the peripheral nerve sheath. It usually occurs in the head and neck; however, it is rare in the oral cavity. The tongue is the most common site of intraoral schwannomas, followed by the floor of the mouth, palate, gingiva, vestibular mucosa, lips and mental nerve area. We report a rare case of schwannoma in the midline of hard palate with ulcerated surface in a 21-year-old male with a twomonth history of a painless swelling on his palate. Clinical, radiographic and histopathological features along with differential diagnosis and treatment are also discussed.